Immunohistochemical studies of Langerhans cells and Thy-1 positive cells in mouse tongue epithelium subjected to local hyperthermia - TOHNAI, Iwai; MITSUDO, Kenji; KOBAYASHI, Miya; UEDA, Minoru; HAYASHI, Yasushi (Japanese Journal of Oral and Maxillofacial Surgery, 2001)
Hyperthermia has been used to treat cancer. However, hyperthermia has been shown to suppress skin-associated immune responses. To examine the effect of heat on immunologically responsive cells in oral mucosa, mouse tongue was heated by an implant heating system at 43°C for 20 min. The densities of Langerhans cells and Thy-1 positive cells in mouse lingual epithelium rapidly increased after treatment and then returned to a normal level after 7 days. Light microscopy confirmed that Langerhans cells in the tongue epithelium formed clusters with lymphocytic cells, suggesting an active immune response to hyperthermia.